Clinicians' opinion on massage in the intensive care unit patients - Tomasz Zwoliński; Marta Jaskulak; Konrad Janicki; Bartłomiej Siek; Dominika Batycka-Stachnik; Bartosz Wilczyński; Dominika Szalewska; Kamila Gworys; Piotr Wąż (Frontiers in Pain Research)
IntroductionPhysiotherapy in the Intensive Care Unit (ICU) is a common medical procedure involving mainly elements of mobilisation, electrotherapy and also, in various forms and to a lesser extent, elements of massage. Massage can positively influence the physical and psychological outcomes of the ICU) patients.AimThe study aimed to assess the perception of physiotherapists (PTs), physicians (PHs), and registered nurses (RNs) working in ICU about the possibilities and safety of implementing massage in the process of rehabilitation of ICU patients.MethodsThis multicentre survey was conducted in Poland in three ICUs (Gdansk, Koscierzyna, Krakow). A total of 135 people participated in the study. Of these, 25.9% (35/135) were PTs, 21.5% (29/135) were PHs, and 52.6% (71/135) were RNs. The questionnaires were distributed and collected online (directly by respondents to Google Form system) and in written form.ResultsMost PTs—71% (25/35)—perceive massage as a beneficial and safe treatment while working with ICU patients. PHs 96% (28/29) and RNs 92% (65/71) also recommend using massage by physiotherapists to rehabilitate ICU patients. In the respondents' opinion, the possibilities for the use of massage by PHs and RNs are lower (between 20% and 55%).ConclusionsAccording to the surveyed clinicians working in the ICU, massage is a safe form of treatment, especially when performed by PTs and it could be a permanent element of rehabilitation among ICU patients, especially for reducing pain, anxiety and restlessness and also improving sleep quality and bowel movement.